14-(5m+4)=3+3m-17

Simple and best practice solution for 14-(5m+4)=3+3m-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14-(5m+4)=3+3m-17 equation:


Simplifying
14 + -1(5m + 4) = 3 + 3m + -17

Reorder the terms:
14 + -1(4 + 5m) = 3 + 3m + -17
14 + (4 * -1 + 5m * -1) = 3 + 3m + -17
14 + (-4 + -5m) = 3 + 3m + -17

Combine like terms: 14 + -4 = 10
10 + -5m = 3 + 3m + -17

Reorder the terms:
10 + -5m = 3 + -17 + 3m

Combine like terms: 3 + -17 = -14
10 + -5m = -14 + 3m

Solving
10 + -5m = -14 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
10 + -5m + -3m = -14 + 3m + -3m

Combine like terms: -5m + -3m = -8m
10 + -8m = -14 + 3m + -3m

Combine like terms: 3m + -3m = 0
10 + -8m = -14 + 0
10 + -8m = -14

Add '-10' to each side of the equation.
10 + -10 + -8m = -14 + -10

Combine like terms: 10 + -10 = 0
0 + -8m = -14 + -10
-8m = -14 + -10

Combine like terms: -14 + -10 = -24
-8m = -24

Divide each side by '-8'.
m = 3

Simplifying
m = 3

See similar equations:

| -10=-n-4n | | 4t=3t-8 | | 14-5m+4=3+3m-17 | | 4-8=-5(1-u) | | 36x^2-42x+49=0 | | x+3=4x-33 | | 8x+8+5=-19 | | -6x^2=-7x-8 | | 2d+7=d-7 | | 0.055(x+4000)=0.08+0.04(2000) | | 4a^2-52a+144=0 | | 5+6x=x+65 | | 5x+41-6x=1-7x+4 | | 56.08+57.98= | | 96=+4(6x-6) | | 2-5r+2r^2=0 | | 2x^2+6+2x=0 | | 32c+3=15+26c | | 10y-7y-7=47.57 | | 0.6x-0.3(3)=4.5 | | X^3-2x^2-19x+20=5 | | U+7=11 | | q^2+2q=-1 | | 3x^2+49+77=0 | | 8(w-7)=5w-29 | | 3x-5(3-x)=7x+21-5+x | | 5x+6=4(x-2) | | 7(e-8)=98 | | 3(x+7)+6(2x+3)=69 | | 4v-2=5v-6 | | 3x-7x=37 | | 2y-12=12-2p |

Equations solver categories